2007
DOI: 10.1063/1.2805634
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low energy single ion impacts in micron scale transistors at room temperature

Abstract: [7]. Donor electron and nuclear spins are promising candidates for implementation of quantum bits in silicon [7]. The detection of low energy single ion impacts for device integration has been accomplished via detection of secondary electrons [2,4,9], or by collection of electron holepairs in optimized diodes [3]. It is also well known that high energy (MeV) single ion impacts can upset device currents [10], and an extension of this approach to low energy ions was recently outlined in Ref. 11. Also, random tel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 22 publications
0
53
0
Order By: Relevance
“…The state-of-the-art for low energy single ion detection using a built-in p-i-n diode is signal-to-noise limited to an energy of ~10 keV P ions producing ~10 3 e-h pairs per implanted ion [7]. Batra et al, [10] and Shinada et al, [11] have alternatively demonstrated successful single ion detection by monitoring changes in transistor current after implanting Si, P, Xe, or Sb donors, 30 -70 keV energies, into the channel of micron scale Si transistors. Increased sensitivity to lower energy ions is desirable to decrease straggle below the range of ~10 nm [6,7] for single atom devices such as solid-state quantum bits [12].…”
Section: Introductionmentioning
confidence: 99%
“…The state-of-the-art for low energy single ion detection using a built-in p-i-n diode is signal-to-noise limited to an energy of ~10 keV P ions producing ~10 3 e-h pairs per implanted ion [7]. Batra et al, [10] and Shinada et al, [11] have alternatively demonstrated successful single ion detection by monitoring changes in transistor current after implanting Si, P, Xe, or Sb donors, 30 -70 keV energies, into the channel of micron scale Si transistors. Increased sensitivity to lower energy ions is desirable to decrease straggle below the range of ~10 nm [6,7] for single atom devices such as solid-state quantum bits [12].…”
Section: Introductionmentioning
confidence: 99%
“…[10] Single ion implantation and detection has been reported by a number of groups. [11][12][13][14][15][16][17][18][19] These works are compared in Table I. The table shows the energy and type of implanted ion as well as the target type and detection scheme used.…”
Section: Introductionmentioning
confidence: 99%
“…Low energy single dopant implantation into both micron-scale and nano-scale devices has been reported (indicated by the bold text in Table I). [11,15,19] Deterministic P implantation was achieved by the detection of the electron-hole (e-h) pairs created by the ion impact with an integrated PiN structure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations